Comparative Study of Bacterial Cellulose Film Dried Using Microwave and Air Convection Heating - I. Indriyati; Yuyun Irmawati; Tita Puspitasari (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
An investigation was conducted to analyze and compare the properties of bacterial cellulose (BC) films dried using microwave and air convection heating. Prior to the drying process, 90% of the water content inside the BC pellicles was removed through vacuum filtration. After that, the required drying time was only 3-5 min using microwave heating, 95% shorter than that observed for air convection heating. The properties of the BC sheets were characterized by Fourier transform infrared (FTIR), X-ray diffractometer (XRD), color difference meter, and tensile tester machine. The results showed that the structure of the BC films was the same for the BC films dried by microwave and air convection heating, i.e. cellulose I, as observed from FTIR spectra and XRD diagrams. Moreover, their color (L*, a*, and b* values) and mechanical properties were also almost identical. However, a slightly lower crystallinity and a higher swelling degree were observed for the BC film dried using microwave heating. These results suggest that microwave heating could be an alternative method of drying BC pellicles in order to shorten the processing time and reduce energy consumption when compared to air convection heating.